Factors associated with iva test as early screening for cervical cancer in women of reproductive age - Yunita Liana; Herlina (Science Midwifery, 2023)
The research's purpose is to identify factors associated to inspect visually using acetic acid for detect cervical cancer in women of reproductive age. Cross-sectional research methods were used for the study. The research sample was 98 women of reproductive age with a purposive sampling technique. The research tool was a questionnaire. The Chi-square test was used to analyze the research data. The results showed an association between knowledge and the examination IVA test (ρ-value= 0,001), husband support and the examination IVA test (ρ-value=0,000), health worker support and the examination IVA test (ρ-value=0,000), and distance to health services with the examination IVA test (ρ-value=0,000). Knowledge, husband support, health worker support, and the distance to health services and the examination IVA test are all elements that associated the in fertile women. Based on the results of the study it is expected that women of childbearing age can increase awareness in carrying outi IVA examinations and that health workers can increase the motivation of women of childbearing age in carrying out IVA examinations. Knowledge, husband support, health worker support, and the distance to health services and the examination IVA test are all elements that associated the in fertile women. The implications for the community health centers are to increase the knowledge of husband and wife through health education activities about the importance of IVA examinations and to motivate women of childbearing age to carry out IVA examinations as early detection of cervical cancer.